Holiness Religion: An Anomaly of Sectarian Typologies - Warburton, Rennie (Journal for the scientific study of religion, 1969)
The grouping together of Holiness and Pentecostal religion for purposes of sociological analysis is not justified. Despite the common theological base and forms of anti-worldliness which they share, Pentecostalism and Holiness religion are distinguishable from one another in terms of the types of religious experience they emphasize. Considerable differences are found in the extent to which their doctrines are distinctive, their organizations exclusive, their meetings inspirational, and their following from the lowest social strata. These differences suggest a greater tendency for Pentecostalism than for Holiness movements to generate sects. The differences are attributed primarily to the highly subjective and invisible nature of Holiness religious experience which has few implications for separatism and enables many Holiness movements to remain interdenominational.